2022
DOI: 10.1093/jn/nxab361
|View full text |Cite
|
Sign up to set email alerts
|

Pasta Structure Affects Mastication, Bolus Properties, and Postprandial Glucose and Insulin Metabolism in Healthy Adults

Abstract: Background Structure and protein–starch interactions in pasta products can be responsible for lower postprandial glycemic responses compared with other cereal foods. Objectives We tested the effect on postprandial glucose metabolism induced by 2 pasta products, couscous, and bread, through their structural changes during mastication and simulated gastric digestion. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…These boluses are obtained as a consequence of deficient mastication and are frequently noted in elderly people with impaired dental status and oral functions (Peyron et al, 2021). Similar results with bread were observed by Vanhatalo et al (2022), who performed a mastication trial involving 26 normal-weight adults. Moreover, the proportion of large particles significantly increased when simulating saliva reduction together with loss of force, which lowers the exchanges between bread boluses and saliva and impedes or delays the initiation of oral digestion of starch (Alam et al, 2019;Blanquet-Diot et al, 2021;Bornhorst, Kostlan, & Singh, 2013).…”
Section: Impact Of Mastication On Nutrient Bioaccessibilitysupporting
confidence: 66%
See 1 more Smart Citation
“…These boluses are obtained as a consequence of deficient mastication and are frequently noted in elderly people with impaired dental status and oral functions (Peyron et al, 2021). Similar results with bread were observed by Vanhatalo et al (2022), who performed a mastication trial involving 26 normal-weight adults. Moreover, the proportion of large particles significantly increased when simulating saliva reduction together with loss of force, which lowers the exchanges between bread boluses and saliva and impedes or delays the initiation of oral digestion of starch (Alam et al, 2019;Blanquet-Diot et al, 2021;Bornhorst, Kostlan, & Singh, 2013).…”
Section: Impact Of Mastication On Nutrient Bioaccessibilitysupporting
confidence: 66%
“…Nevertheless, the in vitro bread boluses obtained after mimicking deficient mastication showed larger and more compact particles than normal masticated bread boluses. The quantity of salivary α-amylase in a food bolus is crucial for the overall breakdown of starch in starch-based products as breads (Bornhorst & Singh, 2012;Vanhatalo et al, 2022). The larger particles noted in poorly fragmented boluses might impair the access of salivary α-amylase to starch granules, impeding or delaying oral digestion of starch and D-glucose release.…”
Section: Impact Of Mastication On the Structural Changes Of Nutrients...mentioning
confidence: 99%
“…In addition, longer chewing duration leads to an increase in the number of food particles that are smaller in size and a larger bolus surface area, which stimulates more saliva production and greater saliva uptake by bolus particles. 8,22 Previous studies have reported that starch digestion increases when food particle size reduces and bolus surface area increases, 10,38 which stimulates greater amylase activity and early glucose release. Experiments on mixed meal tolerance test demonstrated that increasing mastication supports early glucose release and stimulates insulin secretion, 10,16 which suggests that greater bolus saliva uptake could change the kinetics of glucose release and may aid insulin release 8 .…”
Section: Discussionmentioning
confidence: 99%
“…10,20 The sizes of formed bolus particles have also been shown to influence postprandial response, whereby smaller food bolus particles led to a higher blood glucose response among healthy individuals. 21,22…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation